Penanaman Nilai-Nilai Karakter Komunitas Rumah Inklusif Kebumen dengan Paradigma Sembilan Nilai Utama Gus Dur - Umi Arifah; Kholilatus Salma; Sulis Rokhmawanto (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2021)
This research uses qualitative research with a case study approach to the Rumah Inklusif Kebumen Community with data collection techniques through observation, interviews, and documentation. All data were analyzed using the field analysis model, with the flow of data reduction, data presentation, and drawing conclusions. The results of this study can be concluded that the inculcation of character values ​​carried out by the Rumah Inklusif Kebumen Community is seen using the paradigm of Gus Dur's nine main values ​​related to monotheism, humanity, justice, equality, liberation, simplicity, chivalry, and traditional wisdom. Based on these nine values, the character values ​​that are instilled in the Rumah Inklusif Kebumen Community include independence, responsibility, religious, tolerance, hard work, creative, independent, democracy, curiosity, national spirit, love for the homeland, respect for achievement, friendly or communicative, love peace, care for the environment, and care for society.